Lehman Brothers - McDonald, Oonagh (Manchester University Press, 2016)
"On September 12th 2008, Lehman Brothers was valued at 639 billion US dollars. On Monday 15th September, it was worth nothing. How could trillions of dollars seemingly melt into air? Lehman Brothers had a long and prestigious history, and certainly until the end of 2007 had appeared to be conducting a very successful business. Its collapse was the largest bankruptcy in American history and is widely regarded as a crucial event in triggering the turmoil in the markets that triggered the global financial crisis. In this book, Oonagh McDonald, the author of Fannie Mae and Freddie Mac, unravels the events of that fateful September weekend. Using extensive documentary evidence and interviews with former Lehman employees, she reveals the decisions that led to Lehman's collapse, looks at why the government refused a bail-out and whether the implications of this refusal were fully understood. In clear and accessible language she demonstrates both the short and long term effects of Lehman's collapse. This is a fascinating story, with very wide implications. In particular, it raises vital questions about virtual capital and artificial value. McDonald uses her study of the Lehman collapse to examine what is meant by economic value and how it should be identified and measured."